2022
DOI: 10.1161/jaha.122.025644
|View full text |Cite
|
Sign up to set email alerts
|

Causal Association of Cardiovascular Risk Factors and Lifestyle Behaviors With Peripheral Artery Disease: A Mendelian Randomization Approach

Abstract: Background We investigated the causal associations between the genetic liability to cardiovascular and lifestyle risk factors and peripheral artery disease (PAD), using a Mendelian randomization approach. Methods and Results We performed a 2‐sample inverse‐variance weighted Mendelian randomization analysis, multiple sensitivity analyses to assess pleiotropy and multivariate Mendelian randomization analyses to assess mediating/confounding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…The MR design has been used to investigate the potential causal associations of lifestyle factors, including smoking, alcohol and coffee consumption, physical activity, and sleep patterns, with risk of CVD. A consistent association has been reported for genetic liability to smoking with increased risk of most CVDs, 48 , 59 , 73–75 with the strongest magnitude of association observed for peripheral artery disease and abdominal aortic aneurysm. 73–75 …”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The MR design has been used to investigate the potential causal associations of lifestyle factors, including smoking, alcohol and coffee consumption, physical activity, and sleep patterns, with risk of CVD. A consistent association has been reported for genetic liability to smoking with increased risk of most CVDs, 48 , 59 , 73–75 with the strongest magnitude of association observed for peripheral artery disease and abdominal aortic aneurysm. 73–75 …”
Section: Introductionsupporting
confidence: 74%
“… 24 A non-linear MR analysis in the UK Biobank showed that light alcohol drinking was associated with a minimal increase in coronary artery disease risk and that the risk increased exponentially at higher intakes. 78 Mendelian randomization studies have provided suggestive evidence that genetically predicted higher alcohol consumption is associated with increased risk of abdominal aortic aneurysm, 27 atrial fibrillation, 27 , 78 heart failure, 78 and peripheral artery disease 27 , 59 but not with aortic valve stenosis and venous thromboembolism 27 in European populations.…”
Section: Introductionmentioning
confidence: 99%
“…This observation implied that education level is an important upstream factor in determining health outcomes. It is plausible that a higher education level promoted the adoption of healthier lifestyle choices, consequently reducing the likelihood of being exposed to various health risks [33,34]. Secondly, the data from previous studies were obtained on the basis of self-reported cheese intake.…”
Section: Discussionmentioning
confidence: 99%
“…This observation implied that education level is an important upstream factor in determining health outcomes. It is plausible that a higher education level promoted the adoption of healthier lifestyle choices, consequently reducing the likelihood of being exposed to various health risks [29][30]. Secondly, the data from previous studies were obtained based on self-reported cheese intake.…”
Section: Discussionmentioning
confidence: 99%